Use of polymerase chain reaction for detection of adenovirus in children with or without wheezing - Saçkesen, Cansin; Pinar, Ahmet; Sekerel, Bülent E; Akyön, Yakut; Saraçlar, Yildiz (The Turkish Journal of Pediatrics, 2005)
Eighty percent of asthma attacks in children are accompanied by an upper respiratory tract viral infection. Adenovirus is one of the major viral causes of childhood bronchiolitis. As the polymerase chain reaction (PCR) is the most sensitive technique for documenting viral respiratory infections, the PCR method was performed on the throat swab samples of asthmatic children with and without wheezing to investigate the presence of the adenovirus genome in the upper respiratory tract. The frequencies of adenovirus in asymptomatic and symptomatic asthmatic patients, healthy controls and wheezy children were as follows: 33.3%, 71.4%, 37% and 62.96%, respectively. The adenovirus was detected in a significantly higher percentage in the upper airways of patients with asthma exacerbation and in children with wheezing than in patients without asthma exacerbation and in the healthy controls (p < 0.05). The frequency of adenovirus was not different between asthmatic patients receiving or not receiving inhaled corticosteroid. Adenovirus has the potential to precipitate asthma exacerbations in asthmatic patients; its frequency was not affected by the treatment of inhaled corticosteroid.